Annapolis Autumn : Life, Death, And Literature At The U.S. Naval Academy. - Fleming, Bruce (New Press, 2011)
What really goes on behind the wall that surrounds the United States Naval Academy in Annapolis? What are all those midshipmen, future officers in the U.S. Naval and Marine Corps and leaders of our society, thinking as they stand in neat ranks at the parades beloved by tourists? What are their professors actually educating them to do. In Annapolis Autumn, Bruce Fleming, professor of English for nearly two decades at the academy and a prizewinning author, captures the sights, sounds, colors, and conversations of this tradition-steeped institution. In other classes, the cadets learn how to assem.